Optimization of HR Education and Training for Village Fund Managers - Faizal Marzuki; Alfaith S. Manggabarani; Munasiron Miftah (JTP - Jurnal Teknologi Pendidikan, 2020)
This study aims to describe the optimization of village fund processing to realize the dsa mandini community in the Cileles sub-district of Lebak Banten. The research method used is descriptive with a qualitative approach. The result that will be achieved is to create the concept of a village head apparatus who has a strong will to build his village into a mandini village. The main factor is building human resources and utilizing a friendly and hard-working community culture in people's lives. This is a capital that can be developed by the village head in building his village in mutual cooperation. From the results of this study it was concluded that the head of the village in utilizing village funds, could not be implemented optimally by the village, because the village planning proposal had not been fully approved by the district government which made changes to the village proposal, the change was not necessarily in accordance with the needs of the development his village, as a result village must accept changes even if it is not as expected by the village. Such a change certainly does not allow the village to respond quickly, resulting in delays in receiving village funds and automatically the village development program will be too late. besides the lack of resources (HR) that have the skills needed by the village to go to the village of Mandani.